Towards Paradigm of Education Appropriate to the Transition of Contemporary Way of Thinking - Matonis, Vaidas (Pedagogika, 2014)
The purpose of the article is to show the problem of today to educate multi-dimensional man with positively oriented way of thinking in the context of tendencies of European cultural development and globalization. Research objectives are: 1) to disclose the weaknesses of some aspects both of Frankfurt school social theory, and globalization in changing traditional cultural elements and ways of thinking. 2) To found the perspectives of the education of understanding multi-dimensional man. 3) To give an educational interpretation of factors of mind changing in pursuance to promote cultural awareness of growing generation. The aim of protected purposeful education is to form integrated multi-dimensional man, disposing such features as cognoscibility and sensibility, creativity and enterprisebility, interpersonal / intercultural communicability and respectability, critical thinking and responsibility, cultural continuity and cultural awareness. Author is convinced that education of understanding multi-dimensional man which could enter both good traditions of cultural continuity and cultural dialog with the past is able to up-to-date the expression of human spiritual world as well as is possible to increase the sense of responsibility.